Barriers to Modern Contraceptive Use in Kinshasa, DRC - Muanda, Mbadu; Gahungu Ndongo, Parfait; Taub, Leah D.; Bertrand, Jane T. (PLOS ONE, 2016)
Recent research from Kinshasa, DRC, has shown that only one in five married women uses modern contraception; over one quarter have an unmet need for family planning; and almost 400 health facilities across Kinshasa report that they provide modern contraception. This study addresses the question: with reasonable physical access and relatively high unmet need, why is modern contraceptive prevalence so low? To this end, the research team conducted 6 focus groups of women (non-users of any method, users of traditional methods, and users of modern methods) and 4 of husbands (of users of traditional methods and in non-user unions) in health zones with relatively strong physical access to FP services. Five key barriers emerged from the focus group discussions: fear of side effects (especially sterility), costs of the method, sociocultural norms (especially the dominant position of the male in family decision-making), pressure from family members to avoid modern contraception, and lack of information/misinformation. These findings are very similar to those from 12 other studies of sociocultural barriers to family planning in sub-Saharan Africa. Moreover, they have strong programmatic implications for the training of FP workers to counsel future clients and for the content of behavior change communication interventions.